PELESTARIAN PAKAIAN ADAT DAN PERMAINAN TRADISIONAL MELAYU RIAU - Safaruddin Marpaung; Habibul Hakim Habibul; Puaddi; Firdaus Jimmi Pasaribu; Yasnel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Provinsi Riau is a province in Indonesia located on the east coast of the central part of Sumatra Island. Its coastal area borders the Selat Malaka (Malacca Strait). Until 2004, this province also included the Kepulauan Riau (Riau Islands), a large group of small islands (the main islands include Pulau Batam and Pulau Bintan) situated to the east of Sumatra and south of Singapore. These islands were separated to become their own province in July 2004. The capital and largest city of Provinsi Riau is Pekanbaru, and the next largest city after Pekanbaru is Dumai. Currently, Riau is one of the richest provinces in Indonesia, with its resources dominated by natural sources, especially petroleum, natural gas, rubber, palm oil, and fiber plantations. Along with the abundance of its natural resources, Riau is also well known for being rich in traditions and culture, both physical and non-physical, which are inherent in the Masyarakat Riau (Riau community) itself. One of the physical cultures in Riau is the traditional Malay clothing of Riau and its traditional games. The community in Riau is dominated by the Malay ethnic group, which is also influenced by the Malay cultures in Sumatra, Malaysia, and Singapore due to the proximity of the regions. This is marked by similarities in clothing styles that have their own distinct characteristics. The Riau community usually wears their traditional clothing during major events, such as traditional ceremonies, public holidays, official events, as well as traditional games that are commonly seen among the community.